2016
DOI: 10.15420/ecr.2016:26:1
|View full text |Cite
|
Sign up to set email alerts
|

Management of Refractory Angina Pectoris

Abstract: Refractory angina (RA) is conventionally defined as a chronic condition (≥3 months in duration) characterised by angina in the setting of coronary artery disease (CAD), which cannot be controlled by a combination of optimal medical therapy, angioplasty or bypass surgery, and where reversible myocardial ischaemia has been clinically established to be the cause of the symptoms. 1 In clinical practice, patients diagnosed with RA are a heterogeneous group; common among them, however, is that they remain significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 98 publications
(68 reference statements)
0
15
0
6
Order By: Relevance
“…Patients with refractory angina pectoris (RAP) experience chronic symptoms, characterized by chest pain, in the setting of coronary artery disease (CAD), which is uncontrolled despite optimized therapy 1,2 . In the European guidelines CAD is categorized as either acute coronary syndrome or chronic coronary syndrome, with RAP in the latter category 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with refractory angina pectoris (RAP) experience chronic symptoms, characterized by chest pain, in the setting of coronary artery disease (CAD), which is uncontrolled despite optimized therapy 1,2 . In the European guidelines CAD is categorized as either acute coronary syndrome or chronic coronary syndrome, with RAP in the latter category 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of RAP is 5–10% in stable CAD, 4‐5 with a yearly incidence of 50 000–100 000 in the US and 30 000–50 000 in Europe 4,6 . This heterogeneous group remains significantly limited in daily life despite revascularization and optimized medication 2 . Many are not considered for further revascularization when deteriorating in angina symptoms due to unsuitable anatomy, a negative risk–benefit profile, or advanced age 4 .…”
Section: Introductionmentioning
confidence: 99%
“…For chronic angina pain, treatment will typically involve conservative options, such as lifestyle modifications and pharmacologic therapies. Medications may include beta-blockers, calcium channel blockers, and other vasodilators, in addition to less common medications (4). It is worth mentioning, however, that no prior placebo-controlled randomized controlled trial has shown significant improvement in symptoms or quality of life in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…This the first time that a patient has been treated with pharmacological intervention to cure coronary artery disease, the patient had CABG and PTCA but also had refractory angina [3,4]. Patient was not advised PTCA or CABG by her cardiologist after last angiogram [1,5,6].…”
Section: Introductionmentioning
confidence: 99%